Moon Lake : An East Texas Gothic - A Novel - Lansdale, Joe R., 1951- (New York : Mulholland Books/Little, Brown and Company, 2021)
"Daniel Russell was only thirteen years old when his father tried to kill them both by driving their car into Moon Lake. Miraculously surviving the crash and growing into adulthood, Daniel returns to the site of this traumatic incident in the hopes of recovering his fathers car and bones. As he attempts to finally put to rest the memories that have plagued him for years, he discovers something even more shocking among the wreckage that has ties to a twisted web of dark deeds, old grudges, and strange murders"--
"A novel"--Jacket.
Keywords: Fathers and sons -- Fiction; Suicide -- Fiction; Murder -- Fiction; Small cities -- Texas; Fiction; Texas, East -- Fiction; Thrillers (Fiction)